2020
DOI: 10.1104/pp.19.01340
|View full text |Cite
|
Sign up to set email alerts
|

EXO70A2 Is Critical for Exocyst Complex Function in Pollen Development

Abstract: A pollen-specific component of the exocyst, a protein complex regulating cellular secretion, plays an important role in pollen development and function in Arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 89 publications
2
23
0
Order By: Relevance
“…Abnormal swelling of the tip-shape morphology was observed only exceptionally in YFP:EXO70A2-expressing pollen tubes. Our data for Arabidopsis EXO70A2 ( Marković et al, 2020 ) show that this isoform is evolutionarily adapted to positively support pollen development, germination and pollen tube growth. Its interference with pollen tube growth of tobacco might be a result of the competition of endogenous tobacco EXO70A2 with the ectopically overexpressed Arabidopsis EXO70A2 for functional exocyst assembly.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Abnormal swelling of the tip-shape morphology was observed only exceptionally in YFP:EXO70A2-expressing pollen tubes. Our data for Arabidopsis EXO70A2 ( Marković et al, 2020 ) show that this isoform is evolutionarily adapted to positively support pollen development, germination and pollen tube growth. Its interference with pollen tube growth of tobacco might be a result of the competition of endogenous tobacco EXO70A2 with the ectopically overexpressed Arabidopsis EXO70A2 for functional exocyst assembly.…”
Section: Discussionmentioning
confidence: 80%
“…Arabidopsis EXO70A2, another EXO70 subunit highly expressed in pollen, was used as an alternative control ( Marković et al, 2020 ). We found that it also partly inhibited the speed of elongation and expansion but significantly less than EXO70C2 ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations